Descriptive statistical analysis based on patients EEG energy in coma and quasi-brain-death state - Miao, Yao; Cao, Jianting (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2018)
In this paper, measure of descriptive statistical analysis based on EEG (electroencephalography) energy was proposed to evaluate coma and quasi-brain-death patients EEG. Firstly, 36 cases of EEG (coma: 19; quasi-brain-death: 17) were analyzed. Specifically, 60s EEG data of each case were randomly selected and processed to get energy data by Dynamic 2T-EMD (turning tangent empirical mode decomposition), then energy data for 36 cases of EEG obtained were grouped and analyzed by using descriptive statistical analysis, and finally results were displayed by visual method. Results show significantly that energy for coma patients EEG is higher than that for quasi-brain-death patients EEG. And the EEG energy data set for quasi-brain-death is relatively more concentrate.